Levels of practical skills in basic electronic laboratory: students' perceptions - Radin Salim, Kamilah (IEEE, 2011)
Laboratory courses are essential in engineering education in preparing students for engineering experience and practice. Through laboratory experiments, students could develop and enhance their knowledge and skills in the relevant engineering field. In the laboratory, students learn by doing, by practicing engineering skills that they might perform in the future. What are students' perceptions on the levels of practical skills acquired after conducting the laboratory experiments? This paper investigates students' perception on the practical skills acquired after conducting laboratory experiment for one semester. The survey was administered at the end of the semester using Skill Assessment Form. The results indicate some variations in students' perception with regards to their ability in recognizing the electronic components, constructing the circuit, operating the instruments and interpreting the measurement.